Some concerns about copyright protection on the Internet - Barrantes Calderón, Victor J (2007)
The advent of the World Wide Web and the use of technology in the digital environment posed new challenges to copyright. These concerns have been addressed in recent international treaties, so the warning of those who postulate that the Internet is a "no-man's land" where works are completely unprotected is not true. Educating on the subject of copyright protection and providing resources to the bodies in charge of enforcing these rights seems an urgent task.